PRESCRIPTION PATTERN IN OBESE AND NON-OBESE INFERTILE WOMEN WITH POLYCYSTIC OVARY SYNDROME IN A TERTIARY CARE HOSPITAL - Mm, Asha Avirah; Alias, Aswathy; Sajith, Manjusha; Nimbargi, Vandana; Kumdale, Shivhar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to evaluate the treatment options for the management of obese and non-obese infertile women with polycystic ovary syndrome (PCOS). Methods: A prospective observational study was conducted with 75 infertile PCOS women. The demographic details, body mass index, menstrual patterns, and current medication related to infertility were noted. The collected data were statistically represented in terms of range, frequency tables, and standard deviation wherever appropriate. Results: A majority of the infertile PCOS women were aged 24–27 years with a mean age of 25.72±3.53 years, belonging to middle socioeconomic class (44%) and mostly found to be urban residents 68%. Most of the PCOS women were overweight (32%) and obese (21%) with irregular menstrual pattern (90.67%). In combination therapy, clomiphene citrate (CC) pre-treated with oral contraceptives (OC) (37.93%) was mostly given to obese PCOS patients followed by CC with metformin pre-administered with OC (31.03%), whilen on-obese PCOS patients were mostly administered CC with gonadotropins pre-treated with OC(44%). In single therapy, OC was mostly administered to both non-obese (90%) and obese PCOS patients (88.90%). Conclusion: This study concluded that most of the infertile PCOS women were overweight and obese, a major risk actor causing hyperandrogenicity. CC pre-treated with OC and metformin with CC pre-treated with OC were mostly prescribed to obese PCOS patients. Lifestyle modifications along with treatment are strongly recommended, especially in obese PCOS patients.